Lulu goes to witch school - O'Conner, Jane; Sinclair, Bella (London : Harper Collins Publishers, 2013)
A city of Whos on a speck of dust are threatened with destruction until the smallest Who of all helps convince Horton's friends that Whos really exist.
Keywords: Schools; Witches